Autonomous vehicles Regulatory Challenges and the Response from UK and Germany - Kouroutakis, Antonios (Mitchell Hamline School of law, 2020)
The looming dominance of autonomous vehicles has an impact on well-established areas of human activity such as the architecture of the cities and the transportation system. At the legal front, laws at the national and international level have become obsolete as technological changes have created new realities. At the same time, such technology development is challenging long established principles of privacy, tort law, civil liability, criminal law, and insurance law. Nowadays a number of countries, like Germany and the UK, have adopted legislation to allow the operation of autonomous vehicles, while others have been more reluctant. Lawmakers, in their effort to meet the fast technological pace, face a number of challenges. The question is how they decide to solve them. This article examines how lawmakers respond to the presence of autonomous vehicles. In particular, it focuses on the recent legal framework adopted by Germany and the UK. By employing comparative methodology, this article evaluates the legislative initiatives from both Germany and the UK and underpins best practices that would be useful for lawmakers who intend to adopt laws regulating autonomous vehicles. Interestingly, the approaches on some core issues, such as the definition, standards, and characteristics of autonomous vehicles and the requirement for human oversight differ, but both legislative bodies decided to enact laws subject to a two-year review, which signals the experimental character of the laws.
Keywords: ODS 9 - Industria, innovación e infraestructura